Fixing apparatus and electrophotographic image forming apparatus
By using multiple PFA spherical crystals and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers in the surface layer of the fixing film of the fixing equipment, the chemical crack problem caused by fluorinated oil is solved, and the long-term high-quality image of the equipment is achieved Formation and wear resistance.
Patent Information
- Application Number
- CN202410826767.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-27
- Filing Date
- 2024-06-25
- Publication Date
- 2024-12-27
AI Technical Summary
In fixing equipment, the lubricant of the fluorinated oil may cause cracks in the surface layer of the fluorinated resin, affecting the long-term use of the equipment and high-quality image formation.
Using a fixing film with an annular shape, the surface layer contains tetrafluoroethylene-perfluoroalkylvinyl ether copolymer (PFA), and absorbs during the heating process in the endothermic curve measured by a differential scanning calorimeter (DSC). The heat is 21 J/g or more, and the surface layer includes a plurality of spherical crystals of PFA to inhibit the occurrence of chemical cracks.
The fixing equipment that forms high-quality electrophotographic images for a long time is realized, which improves the wear resistance and durability of the equipment, and prevents the occurrence of chemical cracks.
Smart Images

Figure CN119200358A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a fixing device and an electrophotographic image forming apparatus. Background Art
[0002] As a fixing member for a heating and fixing device of an electrophotographic image forming device such as a printer, a copier, and a fax machine, there is a film-shaped or roller-shaped fixing member. As these fixing members, a fixing member in which an elastic layer made of a heat-resistant rubber or the like is optionally formed on a film-shaped or roller-shaped substrate made of a heat-resistant resin or a metal, and a surface layer of the fixing member contains a fluororesin having excellent releasability to a toner is known. Here, as the fluororesin to be contained in the surface layer, a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) excellent in heat resistance is preferably used.
[0003] In addition, from the viewpoint of energy saving promotion, a film heating type fixing device that performs heating via a fixing film having a small heat capacity, that is, a film fixing device, has recently been proposed as an on-demand fixing device having high heat transfer efficiency and quick device startup. Japanese Patent Application Publication No. S63-313182 and Japanese Patent Application Publication No. H02-157878 disclose a film fixing device, which includes, for example, a ceramic heater (hereinafter referred to as a "heater") as a fixed and supported heating body, for example, a heat-resistant resin film (hereinafter referred to as a "fixing film") as a heat transfer member that slides together with the heater, and an elastic pressure roller as a pressure member that is pressed with the heater via the fixing film to form a fixing roller gap portion as a colorant image heating and fixing area, wherein a recording material carrying an unfixed colorant image is clamped and conveyed between the fixing film and the pressure roller in the fixing roller gap portion to heat and melt the unfixed colorant image via the fixing film by heat from the heater, and fix the unfixed colorant image on the recording material.
[0004] In addition, in the fixing devices disclosed in Japanese Patent Application Publication No. 2007-187889 and Japanese Patent Application Publication No. 2005-84225, in order to ensure sliding properties between the fixing film and a member provided in the fixing film so as to contact the inner peripheral surface of the fixing film, a lubricant containing fluorinated oil may be inserted between the fixing film and the member. Summary of the invention
[0005] However, according to the research of the present inventors, when the fixing device is in operation, the lubricant including the fluorinated oil may adhere to the surface layer of the fixing film provided with the surface layer including the fluorine resin such as PFA. At this time, cracks may occur on the surface layer along the direction orthogonal to the circumferential direction of the fixing film. In the surface layer including the fluorine resin, a fluorine resin tube formed by extruding the fluorine resin into a cylindrical shape is generally used.
[0006] In such a fluororesin tube, the fluororesin is crystallized by the molecules of the fluororesin oriented in a direction orthogonal to the circumferential direction. The present inventors have considered that the fluorinated oil enters the intermolecular space of the fluororesin oriented in a direction orthogonal to the circumferential direction and relaxes the bonds between the molecules of the fluororesin to cause cracks. Hereinafter, the tearing on the surface layer at the point where the fluorinated oil is attached is also referred to as "chemical cracking".
[0007] Meanwhile, the present inventors have found that the occurrence of chemical cracks is suppressed on a surface layer formed by melting fluororesin particles attached to an elastic layer or on a surface where a fluororesin tube is heated to a temperature not lower than the melting point of the fluororesin on the surface layer to relax the orientation of the fluororesin. However, the surface layer obtained by these methods has room for improvement in wear resistance, although the occurrence of chemical attack can be suppressed.
[0008] At least one aspect of the present disclosure is directed to providing a fixing device that facilitates long-term formation of high-quality electrophotographic images. At least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus that can form high-quality electrophotographic images for a long period of time.
[0009] At least one aspect of the present disclosure provides a fixing device, comprising:
[0010] A fixing film having a ring shape,
[0011] a pressing member disposed to face the fixing film and configured to form a nip with the fixing film, and
[0012] a heating member disposed inside the fixing film, having an opposing surface facing the inner peripheral surface of the fixing film and configured to cause the fixing film to urge the pressing member, and
[0013] Fluorine grease inserted between the inner circumference and the facing surface,
[0014] The fixing film has at least a base layer, an elastic layer, and a surface layer in sequence.
[0015] The surface layer includes tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA),
[0016] The surface layer includes a plurality of spherulites of PFA, and
[0017] In an endothermic curve measured by a differential scanning calorimeter (DSC) at a temperature increase rate of 20° C. / min using a sample sampled from the surface layer as a measurement sample, the amount of heat absorbed during temperature increase is 21 J / g or more.
[0018] According to at least one aspect of the present disclosure, a fixing device that helps to form high-quality electrophotographic images for a long time can be obtained. At least one aspect of the present disclosure can provide an electrophotographic image forming device that can form high-quality electrophotographic images for a long time. Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a schematic diagram of an image forming apparatus according to one aspect of the present disclosure;
[0020] Figure 2 is a schematic diagram of a fixing device according to one aspect of the present disclosure; and
[0021] Figure 3 is a schematic diagram of a fixing film according to one aspect of the present disclosure. DETAILED DESCRIPTION
[0022] In this specification, unless otherwise stated, the term "from XX to YY" or "XX to YY" indicating a numerical range refers to a numerical range including a lower limit and an upper limit, i.e., an endpoint. In addition, when describing a numerical range in stages, the upper and lower limits of each numerical range can be combined at will. Below, the embodiments of the present disclosure will be described in detail. In addition, the technical scope of the present disclosure is not limited to the following description.
[0023] constitute
[0024] A fixing device comprising:
[0025] A fixing film having a ring shape,
[0026] a pressing member disposed to face the fixing film and configured to form a nip with the fixing film, and
[0027] a heating member disposed inside the fixing film, having an opposing surface facing the inner peripheral surface of the fixing film and configured to cause the fixing film to urge the pressing member, and
[0028] Fluorine grease inserted between the inner circumference and the facing surface,
[0029] The fixing film has at least a base layer, an elastic layer, and a surface layer in sequence.
[0030] The surface layer includes tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA),
[0031] The surface layer includes a plurality of spherulites of PFA, and
[0032] In an endothermic curve measured by a differential scanning calorimeter (DSC) at a temperature increase rate of 20° C. / min using a sample sampled from the surface layer as a measurement sample, the amount of heat absorbed during temperature increase is 21 J / g or more.
[0033] Electrophotographic image forming apparatus
[0034] Figure 1 1 is a cross-sectional view of a color electrophotographic image printer as an example of an electrophotographic image forming apparatus (hereinafter referred to as "image forming apparatus") of this embodiment, and is a cross-sectional view along the conveying direction of a sheet. In this embodiment, the color electrophotographic image printer is simply referred to as a "printer".
[0035] Figure 1 The printer 1 shown is provided with an image forming unit 10 for yellow (Y), magenta (M), cyan (C), and black (Bk). The photosensitive drum 11 is preliminarily charged by a charging device 12. Thereafter, a latent image is formed on the photosensitive drum 11 by a laser scanner 13. The latent image is converted into a toner image by a developing device 14. The toner image on the photosensitive drum 11 is sequentially transferred to an image bearing member such as an intermediate transfer film 31 by a primary transfer blade 17. After the transfer, the toner remaining on the photosensitive drum 11 is removed by a cleaner 15. As a result, the surface of the photosensitive drum 11 is cleaned and ready for the next image formation.
[0036] Meanwhile, the recording material P is sent one by one from the paper feed cassette 20 or the multi-sheet tray 25 in the direction of the arrow 3, and then sent to the registration roller pair 23. The registration roller pair 23 receives the recording material P once, and straightens the recording material P if the recording material is tilted. Then, the registration roller pair 23 is synchronized with the toner image on the intermediate transfer film 31, and sends the recording material P between the intermediate transfer film 31 and the secondary transfer roller 35. The color toner image on the intermediate transfer film is transferred to the recording material P by a transfer body such as the secondary transfer roller 35. Thereafter, when the fixing device 40 presses and heats the recording material P, the toner image on the recording material is fixed to the recording material.
[0037] The electrophotographic image forming apparatus includes a fixing device 40. Next, the fixing device in the electrophotographic image forming apparatus is described. Figure 2 2 is a schematic configuration diagram of the fixing device 40 , and shows an example of a film heating type heating device (tension-free type).
[0038] The fixing device has: a fixing film having an annular shape; a pressing member arranged to face the fixing film and configured to form a roller gap with the fixing film; and a heating member arranged inside the fixing film, having an opposing surface facing the inner peripheral surface of the fixing film, and configured to cause the fixing film to apply force to the pressing member.
[0039] Reference numeral 43 denotes a ceramic heater (hereinafter referred to as a "heater") as a heating body. The heater 43 has a basic structure including an elongated thin plate-shaped ceramic substrate with the vertical direction of the drawing as the length direction and a heating resistor element layer provided on the surface of the substrate that generates heat by energizing. The heater 43 is a low heat capacity heater that raises the temperature as a whole with a sharp rise characteristic by energizing the heating resistor layer. In addition, the heater 43 has a structure that switches the energized area according to the size of the width in the length direction of the recording material.
[0040] The fixing film 41 is a cylindrical (ring-shaped) heat-resistant fixing member as a heating member that transfers heat, and is loosely externally mounted on a supporting member including the above-mentioned heater 43. The fixing film 41 is as shown in FIG. Figure 3 As shown, it is a fixing film having a three-layer composite structure of at least a surface layer 41a, an elastic layer 41c, and a base layer 41d.
[0041] The pressure roller 44 is a heat-resistant elastic pressure roller as a pressure member, and has a core metal and an elastic layer composed of heat-resistant rubber such as silicone rubber or fluorocarbon rubber, or silicone rubber foam. Both ends of the core metal are arranged to be rotatably supported by bearings. That is, the pressure member is preferably a pressure roller.
[0042] On the upper side of the pressure roller 44, the above-mentioned fixing film 41 and the heater 43 are arranged in parallel with the pressure roller 44 on the heater 43 side, and are pressed by a pressing member not shown. That is, the pressure roller is arranged to face the fixing film. The heating member is arranged inside the fixing film, has an opposing surface (hereinafter also referred to as "opposing surface") facing the inner peripheral surface of the fixing film, and is configured to make the fixing film apply force to the pressing member. By doing so, the lower surface of the heater 43 and the upper surface of the pressure roller 44 are pressed against each other via the elasticity of the fixing film 41 against the roller elastic layer, and a fixing roller gap portion with a predetermined width as a heating unit can be formed.
[0043] For example, the pressing member is driven by a driving device (not shown). By driving the pressing member, a driven driving state is established in which the fixing film follows the pressing member and is driven.
[0044] For example, the pressure roller 44 is rotationally driven by a driving member not shown at a predetermined rotational circumferential speed in the counterclockwise direction indicated by the arrow. Due to the rotational drive of the pressure roller 44, a rotational force acts on the cylindrical fixing film 41 through a pressing friction force at the fixing roller nip portion between the pressure roller 44 and the fixing film 41. Then, the fixing film 41 is in a driven rotation state in the clockwise direction indicated by the arrow while the fixing film 41 slides in close contact with the downward facing surface of the heater 43. The supporting member 46 is also a rotation guide member of the cylindrical fixing film 41.
[0045] Therefore, the fixing film 41 slides in contact with the heater 43. At this time, in order to ensure the sliding property between the fixing film 41 and the heater 43, the fixing device includes a fluorine grease (not shown) on the surface of the heater. That is, the fluorine grease is inserted between the inner peripheral surface and the opposite surface of the fixing film. In the fixing device, it can also be said that the fluorine grease is inserted between the heating body 43 and the fixing film. The fluorine grease acts as a lubricant. The use of the fluorine grease makes it possible to maintain lubricity for a long time even under the condition of contact with the heater heated to a high temperature.
[0046] Fluorine grease is not particularly limited, and known fluorine grease can be used. Examples of fluorine grease may include those including fluorine resin particles and fluorinated oil. The fluorine resin contained in the fluorine grease has a function of increasing the retention of the fluorinated oil in the grease due to the swelling of the fluorinated oil. Examples of fluorinated oil may include PFPE and HFE, etc. Examples of fluorine resin may include PTFE, PFA, FEP, etc.
[0047] As a commercially available product, for example, MOLYKOTE HP-300 grease (manufactured by DuPont de Nemours, Inc.) can be used.
[0048] The pressure roller 44 is rotationally driven, and therefore, the cylindrical fixing film 41 is in a driven rotation state. In addition, the heater 43 is energized, and the temperature of the heater is rapidly raised to a predetermined temperature, thereby becoming a state in which the temperature is regulated. In such a state, the recording material P carrying the unfixed toner image T is introduced between the fixing film 41 and the pressure roller 44 in the fixing roller nip portion. Then, at the fixing roller nip portion, the surface of the recording material P on the toner image carrying side is in close contact with the outer surface of the fixing film 41, and the recording material P is clamped and conveyed together with the fixing film 41 through the fixing roller nip portion. The recording material P is heated by the heat of the fixing film 41 that has been heated by the heater 43 during the clamping and conveying process, and the unfixed toner image T on the recording material P is heated, pressurized, melted, and fixed on the recording material P. The recording material P that has passed through the fixing roller nip portion is discharged and conveyed after being separated from the surface curvature of the fixing film 41.
[0049] Numeral 45 denotes a contact thermometer (thermistor) and has a configuration of measuring the temperature of the fixing film 41 heated by the heater 43 and sending the detection result to a temperature control device not shown. Numeral 46 denotes a heater holder, which is a member that holds the heater 43 heated to a high temperature.
[0050] Next, a fixing film constituting a part of the fixing device of the present disclosure will be explained in detail.
[0051] The fixing film according to one embodiment of the present disclosure has at least a base layer, an elastic layer, and a surface layer in sequence. That is, the fixing film has a base layer, an elastic layer on the base layer, and a surface layer on the elastic layer. Other layers may be optionally formed between the base layer, the elastic layer, and the surface layer, as well as on the inner circumferential surface side of the base layer and the outer circumferential surface side of the surface layer. The fixing film may have an annular shape.
[0052] For example, the fixing film 41 may have Figure 3 For example, in Figure 3 , the fixing film has a base layer 41d, an elastic layer 41c covering the outer surface of the base layer 41d, and a surface layer 41a covering the surface opposite to the side of the elastic layer facing the base layer. The surface layer 41a may have a resin layer 41b which is an adhesive layer on the surface on the opposite side of the elastic layer 41c facing the base layer.
[0053] Hereinafter, each layer is described in detail.
[0054] (1) Grassroots
[0055] The material of the base layer 41d is not particularly limited, and a known material used as a base layer can be adopted. For example, metals such as aluminum, iron, stainless steel (SUS), and nickel, alloys, and heat-resistant resins such as polyimide can be used. The material is preferably stainless steel. The thickness of the base layer 41d is not particularly limited, for example, from the viewpoint of strength, flexibility, and heat capacity, preferably from 20 μm to 100 μm, and more preferably from 20 μm to 50 μm.
[0056] The outer surface of the base layer 41d may be treated to impart adhesive properties to the elastic layer 41c. For the surface treatment, physical treatments such as blast treatment, grinding treatment, or polishing, and chemical treatments such as oxidation treatment, coupling agent treatment, or primer treatment may be used alone or in combination with a plurality of types of these treatments.
[0057] If the elastic layer 41c including silicone rubber is formed on the surface of the base layer 41d, it is preferable to perform primer treatment on the surface of the base layer 41d in order to increase the adhesion between the base layer 41d and the elastic layer 41c. Examples of the primer used in the primer treatment may include a coating containing a silane coupling agent, an organic silicon polymer, hydrogenated methylsiloxane, an alkoxysilane, a reaction accelerating catalyst, a colorant such as Bengala, etc., appropriately mixed and dispersed in an organic solvent.
[0058] The primer may be appropriately selected depending on the material of the base layer 41d, the type of the elastic layer 41c, or the manner of the cross-linking reaction. In particular, if the elastic layer 41c contains a large amount of unsaturated aliphatic groups, it is preferable to use a primer containing a hydrosilyl group so as to impart adhesiveness by reaction with the unsaturated aliphatic groups. If the elastic layer 41c contains a large amount of hydrosilyl groups, it is preferable to use a primer containing an unsaturated aliphatic group.
[0059] Other primers may include those containing an alkoxy group. Commercially available primers may be used as the primer. In addition, the primer treatment includes the steps of applying the primer to the outer surface of the base layer 41d (the bonding surface with the elastic layer 41c) and drying or baking the primer.
[0060] (2) Elastic layer
[0061] The material of the elastic layer 41c is not particularly limited, and a known material used as an elastic layer of a fixing film can be adopted. The elastic layer 41c preferably includes silicone rubber having excellent heat resistance. As a raw material of the silicone rubber, an addition-curing liquid silicone rubber is preferably used. For example, the elastic layer 41c can be formed by coating the addition-curing liquid silicone rubber on the outer surface of the base layer 41d and curing the liquid silicone rubber under heating. The coating method is not particularly limited, and any known method can be adopted.
[0062] The thickness of the elastic layer 41c can be appropriately designed in consideration of the surface hardness of the fixing film and the width of the fixing nip portion to be formed. The thickness of the elastic layer is preferably from 100 μm to 1000 μm, and more preferably from 150 μm to 350 μm.
[0063] By maintaining the thickness of the elastic layer within this range, when the fixing film is introduced into a fixing device, a sufficient width of the fixing nip portion can be ensured.
[0064] As the silicone rubber, for example, a cured product of an addition curing type liquid silicone rubber mixture described later can be used. The elastic layer 41c can be formed by applying / heating the liquid silicone rubber mixture by a known method.
[0065] Liquid silicone rubber mixtures usually contain the following components (a) to (d):
[0066] Component (a): an organopolysiloxane having an unsaturated aliphatic group;
[0067] Component (b): an organopolysiloxane having silicon-bonded active hydrogen;
[0068] Component (c): catalyst;
[0069] Component (d): Thermally conductive filler
[0070] Each component will be described below.
[0071] Component (a)
[0072] The organopolysiloxane having an unsaturated aliphatic group is an organopolysiloxane having an unsaturated aliphatic group such as a vinyl group, and examples thereof include those represented by the following formulae (1) and (2). The organopolysiloxane having an unsaturated aliphatic group is preferably a linear type.
[0073]
[0074] In formula (1), m 1 represents an integer greater than 0, and n 1 represents an integer greater than 3. In the structural formula (1), each R 1 independently represents a monovalent unsubstituted or substituted hydrocarbon radical containing no unsaturated aliphatic groups, provided that R 1 At least one of them represents a methyl group, and each R 2 independently represents an unsaturated aliphatic group.
[0075]
[0076] In formula (2), n 2 represents a positive integer, and each R 3 independently represents a monovalent unsubstituted or substituted hydrocarbon radical containing no unsaturated aliphatic groups, provided that R 3 At least one of them represents a methyl group, and each R 4 independently represents an unsaturated aliphatic group.
[0077] In formulas (1) and (2), R 1 and R 3 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group represented by include the following groups.
[0078] -Unsubstituted hydrocarbon
[0079] Alkyl (eg, methyl, ethyl, propyl, butyl, pentyl, and hexyl).
[0080] Aryl (eg, phenyl).
[0081] -Substituted hydrocarbon
[0082] Substituted alkyl (eg, chloromethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, 3-cyanopropyl, and 3-methoxypropyl).
[0083] The organopolysiloxane represented by formula (1) and (2) has at least one methyl group directly bonded to a silicon atom forming a chain structure. However, for ease of synthesis and handling, R 1 and R 3 More than 50% of each is preferably methyl, and more preferably all R 1 and R 3 All are methyl.
[0084] Moreover, in formulas (1) and (2), R 2 and R 4 Examples of unsaturated aliphatic groups represented by include the following groups. Examples of unsaturated aliphatic groups include vinyl, allyl, 3-butenyl, 4-pentenyl, and 5-hexenyl. Among these groups, R 2 and R 4 Both are preferably vinyl groups because synthesis and handling are easy, costs are reduced, and cross-linking reactions are easily performed.
[0085] From the viewpoint of moldability, component (a) preferably has a diameter of from 1000 mm 2 / s to 50000mm 2 / s viscosity. When the viscosity is less than 1000mm 2 / s, it will be difficult to adjust the hardness to the required level of the elastic layer 20c, and when the viscosity is greater than 50000mm 2 / s, the viscosity of the mixture will be too high, making coating difficult. The viscosity (dynamic viscosity) can be measured using a capillary viscometer, a rotational viscometer, or the like in accordance with JIS Z 8803:2011.
[0086] The mixing amount of the component (a) based on the liquid silicone rubber mixture for forming the elastic layer 20 c is preferably 55% by volume or more from the viewpoint of durability, and is preferably 65% by volume or less from the viewpoint of heat conductivity.
[0087] Component (b)
[0088] The organopolysiloxane having silicon-bonded active hydrogen functions as a crosslinking agent which reacts with the unsaturated aliphatic groups of component (a) under the action of a catalyst to form a cured silicone rubber.
[0089] Any organopolysiloxane having Si-H bonds can be used as component (b). In particular, from the viewpoint of reactivity with the unsaturated aliphatic groups of component (a), an organopolysiloxane having an average number of silicon-bonded hydrogen atoms of 3 or more per molecule is preferably used.
[0090] Specific examples of the component (b) include a linear organopolysiloxane represented by the following formula (3) and a cyclic organopolysiloxane represented by the following formula (4).
[0091]
[0092] In formula (3), m 2 Indicates an integer greater than 0, n 3 represents an integer greater than 3, and R 5 Each independently represents a monovalent unsubstituted or substituted hydrocarbon group containing no unsaturated aliphatic group.
[0093]
[0094] In formula (4), m 3 Indicates an integer greater than 0, n 4 represents an integer greater than 3, and R 6 Each independently represents a monovalent unsubstituted or substituted hydrocarbon group containing no unsaturated aliphatic group.
[0095] In formula (3) and (4), R 5 and R 6 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group include the same as those described above for R in the structural formula (1): 1 Among them, preferred is R 5 and R 6 More than 50% of each are methyl groups, and more preferably all R 5 and R 6 All are methyl groups because synthesis and handling are easy and excellent heat resistance is easily obtained.
[0096] Component (c)
[0097] Examples of catalysts for forming silicone rubber include hydrosilylation catalysts for promoting curing reactions. Known substances such as platinum compounds and rhodium compounds can be used as hydrosilylation catalysts. The blending amount of the catalyst can be appropriately set and is not particularly limited.
[0098] Component (d)
[0099] The elastic layer 41c may contain a filler. The filler is added to control thermal conductivity, heat resistance, and elastic modulus. As a thermally conductive filler, a metal, a metal compound, or carbon fiber may be mentioned. A high thermally conductive filler is further preferred, and specific examples thereof may include the following materials.
[0100] Metallic silicon (Si), silicon carbide (SiC), silicon nitride (Si 3 N 4 ), boron nitride (BN), aluminum nitride (AlN), aluminum oxide (Al 2 O 3 ), iron oxide (Fe 2 O 3 )、ZnO、MgO、TiO 2 ), silicon dioxide (SiO 2 ), copper (Cu), aluminum (Al), silver (Ag), iron (Fe), nickel (Ni), carbon black (C), carbon nanotubes (C), vapor-grown carbon fiber, PAN (polyacrylonitrile) carbon fiber, and pitch-type carbon fiber.
[0101] The elastic layer may contain a reaction control agent (inhibitor). By including a reaction control agent, the reaction start time can be controlled. The reaction control agent is not particularly limited, and known substances can be used. Examples thereof may include methylvinyltetrasiloxane, acetylene alcohol, siloxane-modified acetylene alcohol, and hydroperoxide.
[0102] (3) Resin layer
[0103] The resin layer 41b is preferably a layer capable of bonding the surface layer and the elastic layer, and, for example, the resin layer 41b preferably includes a cured product of an adhesive. That is, the resin layer is preferably an adhesive layer. The adhesive may be a solution type adhesive or a hot melt type adhesive.
[0104] The adhesive is not particularly limited, and a known adhesive can be used. Preferably, a silicone rubber adhesive is used, and more preferably, an addition-cured silicone rubber adhesive is used. When the elastic layer contains silicone rubber, the elastic layer also contains an uncrosslinked component. In this case, the inner surface of the surface layer and the uncrosslinked component in the elastic layer react with the uncrosslinked component in the adhesive and are connected to each other by heating, so that the surface layer and the elastic layer can be firmly bonded.
[0105] Examples of addition-cured silicone rubber adhesives may include those having at least one functional group selected from vinyl, SiH groups, and epoxy groups. When the addition-cured silicone rubber adhesive has a vinyl group, the vinyl group reacts with the SiH group, which is an uncrosslinked component that may be included in the elastic layer. When the addition-cured silicone rubber adhesive has a SiH group, the SiH group reacts with the vinyl group, which is an uncrosslinked component that may be included in the elastic layer. When the addition-cured silicone rubber adhesive has an epoxy group, the ring of the epoxy group opens to form an OH group, and the OH group forms a hydrogen bond with the OH group that may be included in the inner surface of the surface layer.
[0106] Specifically, SE 1819CV manufactured by Dow Corning Toray Co., Ltd. in which equal amounts of "Liquid A" and "Liquid B" are mixed can be mentioned.
[0107] (4) Surface layer
[0108] The surface layer 41a contains tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), which is a fluororesin. PFA is a copolymer of perfluoroalkyl vinyl ether (PAVE) and tetrafluoroethylene (TFE). PFA is not particularly limited, and known PFAs can be used. The copolymerization ratio (molar ratio) (PAVE / TFE) between perfluoroalkyl vinyl ether (PAVE) and tetrafluoroethylene (TFE) is preferably 99.5 / 0.5 to 95.0 / 50, and more preferably 99.0 / 1.0 to 95.5 / 4.5. Commercially available PFA can be used as PFA. Specifically, AP-230 (trade name, manufactured by Daikin Industries, Ltd.) and AP-231SH (trade name, manufactured by Daikin Industries, Ltd.) as PFA with fully fluorinated end groups can be mentioned.
[0109] For example, the presence of a characteristic peak of polytetrafluoroethylene (PTFE) can be detected by checking for the presence of a characteristic peak of polytetrafluoroethylene (PTFE) and also checking for a peak at 994 cm-1 that does not appear in PTFE in the ATR spectrum of FT-IR. -1 A small peak nearby confirms the presence of PFA.
[0110] First, the characteristic peak of PTFE is contained at 1200 cm -1 CF 2 Antisymmetric expansion and contraction), at 1150cm -1 CF 2 Symmetrical expansion and contraction), at 640cm -1 CF 2 Out-of-plane bending angle (wagging) at 555cm -1 CF2 In-plane bending angle (scissor type)), and at 505cm -1 CF 2 The peak of the in-plane bending angle (rocking). 994 cm-1, which is characteristic of PFA -1 The position of the peaks near 994 cm-1 varies depending on the length of the carbon chain in the perfluoroalkyl vinyl ether moiety. In the case of perfluoropropoxy, the peak appears at 994 cm-1. -1 In the case of perfluoroethoxy, the peak appears at 1090 cm -1 In the case of perfluoromethoxy, the peak appears at 881 cm -1 Place.
[0111] As means for forming the surface layer 41a containing PFA, there can be mentioned a method comprising coating a dispersion liquid (aqueous dispersion paint) or a powder paint containing PFA as a main component on the surface of the elastic layer 41c and heating it at a temperature not lower than the melting point to form a film. Alternatively, there can also be mentioned a method comprising coating a PFA tube produced separately by extrusion molding on the surface of the elastic layer 41c. For example, the surface layer 41a is a PFA tube.
[0112] In an endothermic curve measured by a differential scanning calorimeter (DSC) at a temperature increase rate of 20° C. / min using a sample sampled from the surface layer as a measurement sample, the amount of heat absorbed during temperature increase is 21 J / g or more.
[0113] Generally, the temperature increase process in the DSC measurement using the sampled sample as the measurement sample can be performed twice or more depending on the purpose of the measurement. If the amount of heat absorbed in the first temperature increase process is 21 J / g when the temperature increase process is performed twice or more, it is considered that the condition "the amount of heat absorbed in the temperature increase process is 21 J / g or more" is satisfied. Therefore, the "amount of heat absorbed in the temperature increase process" can be referred to as the "amount of heat absorbed in the first temperature increase process".
[0114] The amount of heat absorbed during the temperature rise process measured by DSC is the amount of heat absorbed due to the crystal melting of PFA. The crystallinity of PFA can be calculated by dividing the value of the amount of heat absorbed by the heat of complete crystal melting of PFA (92.9 J / g). When the amount of heat absorbed is 21 J / g or more, the abrasion resistance to paper becomes good. When the amount of heat absorbed is 24 J / g or more, the abrasion resistance to paper becomes better.
[0115] The upper limit of the amount of heat absorption is not particularly limited, but the amount of heat absorption is preferably 40 J / g or less, and particularly preferably 27 J / g or less. When the amount of heat absorption is 40 J / g or less, a certain amount of amorphous part of PFA exists in the surface layer, and it becomes easier for the surface layer to better follow the deformation of the elastic layer. The amount of heat absorption during the temperature rise is preferably 21 to 40 J / g, more preferably 21 to 27 J / g, and further preferably 25 to 27 J / g.
[0116] Unless otherwise specified, the measurement of differential scanning calorimetry (DSC) and the analysis of DSC graphs in the present disclosure comply with Japanese Industrial Standard (JIS) K 7121-2012.
[0117] As a method for making the endothermic amount 21 J / g or more, there may be mentioned a method comprising heating the surface layer 41 a after formation to a temperature not lower than the melting point of PFA and controlling the cooling rate to promote crystallization of PFA during production of the fixing member.
[0118] The specific method is not particularly limited, but the following method for heat-treating the surface layer can be used.
[0119] After the surface layer is formed, a vertical cylindrical heating tube that can be heated to, for example, 330° C. or more is used to heat the entire area of the fixing film. For example, a belt heater with a thermocouple is installed in the heating tube to control the heating temperature of the fixing film. The heating temperature is preferably from the melting temperature of PFA to 350° C. As long as the temperature of the surface layer fully reaches the desired temperature, the heating time can be any time, and can be, for example, 1 to 20 minutes, 1 to 10 minutes, and 2 to 5 minutes, etc.
[0120] After the heating is completed, the cooling rate of the heating tube is controlled to control the cooling rate of the fixing member. For example, if an air supply nozzle is formed on the periphery of the heating tube and the air flow rate is adjusted, the cooling rate can be controlled. The slower the cooling rate within the crystallization temperature range of PFA, the more the crystallization of PFA can be promoted, and the cooling rate is preferably adjusted so that the heat absorption is 21 J / g or more. The cooling rate is preferably controlled until the temperature of the surface layer drops below the crystallization temperature range of PFA. The cooling rate can be any rate within the range in which the heat absorption can be controlled to be 21 J / g or more, and is not particularly limited, but can preferably be from 5°C / min to 60°C / min, and more preferably from 10°C / min to 30°C / min.
[0121] In the surface layer 41a, the orientation degree of the PFA molecules in the direction orthogonal to the circumferential direction of the surface layer obtained using the transmission X-ray diffraction method is preferably 35% or less, particularly preferably 34% or less, and further particularly 25% or less. When the orientation degree is 35% or less, the orientation degree of the PFA molecules in the direction orthogonal to the circumferential direction of the fixing film is small. Therefore, even if fluorinated oil is attached, the penetration of fluorinated oil in the direction orthogonal to the circumferential direction of the fixing film can be more reliably suppressed. As a result, the occurrence of chemical cracks along this direction can be prevented for a long time. The lower limit of the orientation degree is not particularly limited, but can be, for example, 0%. The preferred range of the orientation degree is, for example, from 0% to 35%, particularly from 0% to 34%, and more preferably from 0% to 25%.
[0122] The degree of orientation of the surface layer can be adjusted by the conditions of the cylinder molding of the fluororesin. A method for measuring the degree of orientation will be described later.
[0123] The surface layer 41a includes a plurality of spherulites of PFA. When the surface layer 41a includes a plurality of spherulites of PFA, the size of the spherulites is small and the fluorinated oil impregnation is reduced. Therefore, chemical cracks are less likely to occur and the durability against chemical cracks is good. As a method of including a plurality of spherulites of PFA in the surface layer 41a, for example, a method of heat treating the surface layer can be mentioned.
[0124] The presence of spherulites of PFA can be confirmed by the method described below.
[0125] The number of spherulites of PFA is not particularly limited as long as it is plural, and, for example, may be 100 μm per 500 μm. 2 From 2 to 300. When the number is within the above range, durability against chemical cracks tends to be good.
[0126] By using a transmission polarizing microscope, the 500 μm 2 The number of spherulites within the area was counted to determine the number of PFA spherulites.
[0127] The thickness of the surface layer 41a is preferably 100 μm or less. The thickness of the surface layer is more preferably 10 to 100 μm, further preferably 10 to 70 μm, and particularly preferably 15 to 50 μm. When the thickness is within the above range, wear resistance increases.
[0128] The thickness of the surface layer 41a can be measured by a micrometer.
[0129] As a method for adjusting the thickness to be within the above range, for example, the following method may be employed: Here, an example in which a PFA tube is used to produce the surface layer 41a is mentioned, but the surface layer of the present disclosure is not limited to those formed using a PFA tube.
[0130] For example, a PFA tube is produced by extruding molten PFA from a cylindrical die. Such a PFA tube is rapidly cooled during the extrusion process, and crystallization proceeds rapidly. Therefore, the crystals are oriented in the extrusion direction, and the crystallinity is low. The PFA tube is placed as a surface layer 41a to cover the surface of the elastic layer 41c, and then the surface layer is heat-treated to increase the crystallinity, and spherulites are formed on the surface of the surface layer. By increasing the crystallinity, the amount of heat absorbed in the first temperature rise process can be easily controlled to be within the above range.
[0131] In addition, the heat treatment also relaxes the molecular orientation of the PFA tube, and the molecular chains oriented in the extrusion direction become random. In this way, the thermal conductivity in the thickness direction can be increased. At this time, the orientation degree of the PFA tube obtained using the transmission X-ray diffraction method is 35% or less.
[0132] When the inner surface of the surface layer 41a is subjected to sodium treatment, excimer laser treatment, ammonia treatment, or plasma etching treatment, adhesion can be increased. It is preferable to treat the inner surface of the PFA tube using excimer laser treatment.
[0133] As the excimer laser treatment, it is preferred to attach a compound that absorbs ultraviolet light to the inner surface of the PFA tube and irradiate the compound with a UV laser such as a KrF excimer laser or an ArF excimer laser. As the compound that absorbs UV light, a known compound can be used. For example, an aqueous solution containing a mixture of a compound that absorbs UV light such as sodium benzoate and a known fluorochemical surfactant is prepared, and then the solution is applied to the inner surface of the PFA tube and air-dried.
[0134] The irradiation conditions of the excimer laser are generally selected from the viewpoint of improving wettability and adhesion, and the irradiation amount per shot or the number of shots is adjusted. In the present disclosure, it is preferred to sufficiently perform carbonization on the inner surface of the PFA tube by increasing the number of shots more than is usually required. For example, the irradiation amount of the excimer laser is preferably 100 to 600 mJ / cm 2 / pulse, and more preferably 200 to 400 mJ / cm 2 The number of emission is preferably 3 to 10, and more preferably 4 to 8.
[0135] The measurement methods of various properties in the present disclosure are described below.
[0136] Methods for measuring heat absorption
[0137] First, the surface layer was separated from the fixing film. Specifically, the laminate of the elastic layer and the surface layer was peeled off from the substrate. The peeled laminate of the elastic layer and the surface layer was immersed in e-Solve 21RS (manufactured by Kaneko Chemical Co., Ltd.), and then placed in a water tank of an ultrasonic cleaner (trade name: Bransonic (model: 2510J-DTH); manufactured by Emerson Japan, Ltd.), and ultrasonic waves were applied to the laminate for 60 minutes to dissolve the elastic layer.
[0138] After that, the laminate was taken out, washed with water, and wiped with toluene and then with ethanol to separate only the surface layer. All the separated surface layers were used as samples.
[0139] Use differential scanning calorimeter (trade name: Q2000, manufactured by TA Instruments) to measure the amount of heat absorbed. The melting points of indium and zinc are used to calibrate the temperature of the detection unit of the device, and the heat of fusion of indium is used to calibrate the amount of heat. Specifically, 4 mg of the surface layer separated as described above is accurately weighed and placed in an aluminum pan. An empty aluminum pan is used as a reference. Measured within a measurement range from 25°C to 400°C and at a heating rate of 20°C / min. The temperature is raised to 400°C and maintained at the same temperature for 5 minutes, and then the temperature is reduced to 25°C at a cooling rate of 20°C / min. At this point, the area surrounded by the temperature-endothermic heat curve including the endothermic peak and the baseline is taken as the amount of heat absorbed.
[0140] Method for measuring the number of spherulites
[0141] First, the surface layer is separated from the fixing film as described above. Then, the outer surface of the separated surface layer is observed by a polarizing microscope (ECLIPSE LV100NPOL (manufactured by NIKON Corporation)), thereby obtaining an observation image of spherulites. As a condition for observation, a polarizing microscope with 5x and 20x objective lenses is used to observe the fluororesin taken out as a sample. An observation image in which the spherulite structure can be checked can be obtained using a transmission polarizing microscope. From the observation image of the spherulites thus obtained, the number of spherulites is checked, whereby it can be confirmed that the surface layer includes a plurality of spherulites of PFA.
[0142] Orientation measurement of surface layers
[0143] First, the surface layer was separated from the electrophotographic image member. Specifically, a razor was inserted between the elastic layer and the base layer, and the laminate of the elastic layer and the surface layer was peeled off from the base. The laminate of the peeled elastic layer and the surface layer was immersed in e-Solve 21RS (manufactured by Kaneko Chemical Co., Ltd.), and then the laminate was placed in a water tank of an ultrasonic cleaner (trade name: Bransonic (model: 2510J-DTH); manufactured by Emerson Japan, Ltd.), and ultrasonic waves were applied to the laminate for 60 minutes to dissolve the elastic layer.
[0144] Afterwards, take out the laminate, wash with water, and wipe with toluene and then with ethanol to separate only the surface layer. The orientation degree of the surface layer is obtained by calculating the orientation degree by wide-angle X-ray diffraction. The oriented sample has an intensity distribution along the Debye ring, and the X-ray diffraction image is used to measure the orientation degree. By using a fiber sample stage, 2θ is fixed at a peak near 18 °, the sample is rotated 360 ° (β-rotation), and the intensity distribution is measured along the Debye ring. From the intensity distribution obtained, the orientation degree of the surface layer is obtained using the following formula.
[0145] H={(360-ΣW / 360)}×100
[0146] In the formula, H represents the degree of orientation (%), and W represents the half width. The half width refers to the half width of a peak obtained from two peaks derived from the vicinity of 2θ=18°, one peak appears at a β-rotation angle in the range of 0° to 180°, and the other peak appears at a β-rotation angle in the range of 180° to 360°.
[0147] A rotating cathode type X-ray diffraction apparatus RINT 2500 (X-ray: CuKα) was used as an X-ray diffraction apparatus, and measurement was performed at a tube voltage of 40 kV and a tube current of 15 mA.
[0148] Method for measuring the thickness of the surface layer
[0149] The thickness of the surface layer was measured using a high-precision digital micrometer (MDH-25MC, manufactured by Mitutoyo Corporation). The arithmetic mean of 5 measurement points was used as the measurement result.
[0150] Evaluation Method
[0151] Next, the evaluation method in this embodiment is described.
[0152] Evaluation 1: Durability against chemical cracking
[0153] Evaluation was performed using the prepared fixing device. The evaluation conditions were as follows.
[0154] Test environment: room temperature 10℃, humidity 10%
[0155] Processing speed: 280mm / sec
[0156] Printing speed: 60 sheets / min
[0157] Paper feeding conditions: A grid image was formed on GF-C104 (manufactured by Nippon Paper Industries Co., Ltd., 105 g paper, A4 size), and the paper was continuously fed.
[0158] GC-C081 (manufactured by Nippon Paper Industries Co., Ltd., 68 g paper, A4 size) was fed every 100,000 sheets, and the occurrence of scratches in the length direction on the surface layer after the feeding was observed and evaluated according to the following criteria.
[0159] Evaluation Criteria
[0160] Grade A: No scratches occurred even after feeding more than 500,000 sheets of paper Grade B: No scratches occurred even after feeding more than 400,000 sheets of paper Grade C: No scratches occurred even after feeding more than 300,000 sheets of paper
[0161] Grade D: Scratches occur before feeding less than 300,000 sheets
[0162] Evaluation 2: Durability evaluation
[0163] Evaluation of wear resistance
[0164] Evaluation was performed using the prepared fixing device. The evaluation conditions were as follows.
[0165] Test environment: room temperature 25℃, humidity 50%
[0166] Processing speed: 280mm / sec
[0167] Printing speed: 60 sheets / min
[0168] Paper feeding conditions: A grid image was formed on CS-068 (manufactured by Nippon Paper Industries Co., Ltd., 68 g paper, A4 size), and the paper was continuously fed.
[0169] Evaluation Criteria
[0170] A: Almost no scraping was observed on the surface layer even after feeding 500,000 sheets of paper
[0171] B: Almost no scraping was observed on the surface layer even after feeding 200,000 sheets of paper, but after feeding 500,000 sheets of paper, slight scraping caused by the end of the paper was observed on the surface layer. C: Slight scraping was observed on the surface layer after feeding 200,000 sheets of paper, and significant scraping was observed on the surface layer after feeding 500,000 sheets of paper. D: Significant scraping was observed on the surface layer after feeding 200,000 sheets of paper.
[0172] Evaluation of motor torque current value
[0173] In addition to the above evaluation of wear resistance, the motor torque current value during paper feeding was measured every 100,000 sheets fed, and evaluated under the following evaluation criteria: An excellent evaluation of the motor torque current value means that the heat resistance of the grease is excellent.
[0174] Evaluation Criteria
[0175] Level A: Motor torque is less than 2.0A
[0176] Level B: Motor torque is 2.0A or more and less than 2.5A
[0177] Level C: Motor torque is 2.5A or more and less than 3.0A
[0178] Level D: Motor torque is 3.0A or more
[0179] Example
[0180] Hereinafter, the present disclosure is further described in detail using Examples and Comparative Examples, but aspects of the present disclosure are not limited thereto.
[0181] Example 1
[0182] Method for producing fixing film
[0183] In this example, the preparation Figure 3 The fuser film shown.
[0184] Inner surface treatment of PFA tube
[0185] A PFA tube having a thickness of 20 μm obtained by extrusion molding using NEOFLON PFA: AP-231SH (manufactured by DAIKIN Industries) as a raw material was used. An aqueous solution prepared so that sodium benzoate should be 5% by mass and Surflon S-113 (a fluorine-containing surfactant, manufactured by AGC Seimi Chemical Co., Ltd.) should be 1% by mass was applied to the entire surface of the PFA tube and air-dried, and a 300 mJ / cm 26 shots of 1 / 6 pulsed KrF excimer laser were used to obtain a PFA tube with a treated inner surface.
[0186] Grassroots
[0187] SUS having an inner diameter of 24 mm and a thickness of 30 μm was used as the base layer.
[0188] Formation of the inner surface sliding layer
[0189] First, substantially equimolar amounts of aromatic tetracarboxylic dianhydride or its derivative and aromatic diamine are reacted with each other in an aprotic polar organic solvent to obtain a polyimide precursor solution. The obtained polyimide precursor solution is applied to the inner peripheral surface of the base layer by a ring coating method, and then the solvent is dried in an electric furnace, and the coating is heated at a temperature of 260° C. to 400° C. for about 1 hour to form an inner surface sliding layer. The thickness of the inner surface sliding layer is 12 μm.
[0190] Formation of primer layer and elastic layer
[0191] For the base layer having the inner surface sliding layer, the primer layer and the elastic layer are formed according to the following process.
[0192] A hydrosilyl silicone primer (DY39-051A / B; manufactured by Dow Toray Co., Ltd.) was applied to the base layer, and the coating was heated at 200° C. for 5 minutes. A liquid addition-curable silicone rubber mixture containing the following components (a) to (d) was applied to the primer layer in a thickness of 250 μm and then heat-cured at 200° C. for 30 minutes to form a silicone rubber elastic layer having a thickness of 250 μm.
[0193] Silicone rubber mixture
[0194] Component (a): Straight-chain organopolysiloxane having an unsaturated aliphatic group
[0195] Component (b): an organopolysiloxane having silicon-bonded active hydrogen
[0196] Component (c): Catalyst
[0197] Component (d): Thermally conductive filler
[0198] First, as component (a), 100 parts by mass of an organosilicon polymer having only vinyl groups as unsaturated aliphatic groups and methyl groups as unsubstituted hydrocarbon groups containing no other unsaturated aliphatic groups at both ends of the molecular chain was prepared. This organosilicon polymer (trade name DMS-V35, manufactured by Gelest Inc., viscosity: 5000 mm 2 / s) is referred to as "Vi" hereinafter.
[0199] Next, as component (d), 370 parts by mass of alumina (trade name: Alunabads CB-P10, manufactured by Showa Denko KK) was added to this Vi and placed in a planetary centrifugal mixer (manufactured by Thinky Corporation, ARV-5000), and the mixture was stirred and mixed at 600 rpm for 2 minutes to obtain Mixture 1.
[0200] Next, 0.2 parts by mass of a solution of 1-ethynyl-1-cyclohexanol (manufactured by Tokyo Chemical Industry Co., Ltd.) as a curing retarder in the same mass of toluene was added to Mixture 1, whereby Mixture 2 was obtained.
[0201] Next, as component (c), 0.1 parts by mass of a hydrosilylation catalyst (platinum catalyst: a mixture of platinum-1,3-divinyltetramethyldisiloxane, 1,3-divinyltetramethyldisiloxane, and 2-propanol) was added to Mixture 2, whereby Mixture 3 was obtained.
[0202] Furthermore, as component (b), 1.1 parts by mass of an organic silicon polymer having a linear siloxane skeleton and silicon-bonded active hydrogen groups present only in the side chains (trade name: HMS-301, manufactured by Gelest, Inc., viscosity: 30 mm 2 / s, hereinafter referred to as "SiH"). This was added to Mixture 3, and the resulting mixture was thoroughly mixed to obtain a liquid addition-curing silicone rubber mixture.
[0203] Adhesive layer coating
[0204] After the elastic layer was formed, an adhesive (SE 1819CV A / B; manufactured by Dow Toray Co., Ltd.) was coated on the elastic layer using a ring coating method so that the thickness should be 7 μm.
[0205] Surface layer formation
[0206] After coating the adhesive, the PFA tube having the above-treated inner surface was placed to be covered with the adhesive from the outside by a vacuum expansion covering method to produce a surface layer.
[0207] Specifically, a PFA tube is sucked under vacuum conditions on the inner surface of an outer tube having an inner diameter larger than the outer diameter of the workpiece after the elastic layer with the applied adhesive is formed to expand the diameter of the tube, the workpiece is embedded therein, and the vacuum is released so that the PFA tube should cover the adhesive. Extra adhesive and air between the PFA tube and the elastic layer are wiped off with an O-ring or the like, and then the adhesive is cured and bonded with a heating device such as an electric furnace, thereby forming a resin layer. Specifically, a high-temperature electric furnace (Perfect Furnace PHH-201M (manufactured by ESPEC Corp.) is used to heat at 200°C for 5 minutes. Thereafter, both ends are cut into a desired length (350 mm).
[0208] Heating treatment of the surface layer
[0209] Cut both ends to the desired length and insert the tube into the The entire range was heat treated in a heating tube of , and a band heater was used in the heating tube. The heating temperature was set to 330°C, and the heat treatment was performed so that the solid temperature of the surface layer should not be lower than the melting temperature of PFA.
[0210] The heating time, which is the time during which the substantial temperature of the surface layer can sufficiently reach the desired heat treatment temperature, was set to 3 minutes after the fixing film was fed into the heating tube. After the passage of 3 minutes from the start of feeding, the heating tube was cooled to 200° C. at a cooling rate of 20° C. / min. Thereafter, the fixing film was taken out of the heating tube into an atmosphere at normal temperature (25° C.), thereby obtaining a fixing film.
[0211] The physical properties of the obtained fixing film are shown in Table 1.
[0212] The obtained fixing film is used to prepare Figure 2 Here, fluorine grease (trade name: MOLYKOTE HP-300 grease; manufactured by DuPont de Nemours, Inc.) is applied to the inner surface of the base layer 41d to provide fluorine grease (not shown) on the surface of the heating body 43 of the fixing device. Here, "MOLYKOTE HP-300 grease" is a mixture of fluorinated oil and PTFE particles as a thickener.
[0213] The prepared fixing films and fixing devices were subjected to the following evaluations. Table 2 shows the results.
[0214] Method for measuring heat absorption
[0215] First, the surface layer was separated from the fixing film. Specifically, the laminate of the elastic layer and the surface layer was peeled off from the substrate. The laminate of the peeled elastic layer and the surface layer was immersed in a silicone solubilizer (trade name: e-Solve 21RS; manufactured by Kaneko Chemical Co., Ltd.), and then placed in a water tank of an ultrasonic cleaner (trade name: Bransonic (model: 2510J-DTH); manufactured by Emerson Japan, Ltd.), and ultrasonic waves were applied to the laminate for 60 minutes to dissolve the elastic layer. After that, the laminate was taken out, washed with water, and wiped with toluene and then wiped with ethanol to separate only the surface layer. All separated surface layers were used as samples.
[0216] Use differential scanning calorimeter (trade name: Q2000, manufactured by TA Instruments) to measure the amount of heat absorbed. The melting points of indium and zinc are used to calibrate the temperature of the detection unit of the device, and the heat of fusion of indium is used to calibrate the amount of heat. Specifically, 4 mg of the surface layer separated as described above is accurately weighed and placed in an aluminum pan. An empty aluminum pan is used as a reference. Measured within a measurement range from 25°C to 400°C and at a heating rate of 20°C / min. The temperature is raised to 400°C and maintained at the same temperature for 5 minutes, and then the temperature is reduced to 25°C at a cooling rate of 20°C / min. At this point, the area surrounded by the temperature-endothermic heat curve including the endothermic peak and the baseline is taken as the amount of heat absorbed.
[0217] Method for measuring the number of spherulites
[0218] First, the surface layer was separated from the fixing film as described above. Then, the outer surface of the separated surface layer was observed by a polarizing microscope (trade name: ECLIPSELV100N POL (manufactured by NIKON Corporation)), thereby obtaining an observation image of spherulites. As the observation condition, the fluororesin taken out as a sample was observed using a polarizing microscope with 5x and 20x objective lenses. From the observation image thus obtained, the number of spherulites was checked, and it was confirmed that the surface layer contained a plurality of spherulites of PFA.
[0219] Orientation measurement of surface layers
[0220] First, the surface layer was separated from the electrophotographic image member. Specifically, a razor was inserted between the elastic layer and the base layer, and the laminate of the elastic layer and the surface layer was peeled off from the base. The laminate of the peeled elastic layer and the surface layer was immersed in a silicone solubilizer (trade name: e-Solve 21RS; manufactured by Kaneko Chemical Co., Ltd.), and then the laminate was placed in a water tank of an ultrasonic cleaner (trade name: Bransonic (model: 2510J-DTH); manufactured by Emerson Japan, Ltd.), and ultrasonic waves were applied to the laminate for 60 minutes to dissolve the elastic layer.
[0221] Thereafter, the laminated body was taken out, washed with water, and wiped with toluene and then with ethanol to separate only the surface layer.
[0222] The orientation degree of the surface layer is obtained by calculating the orientation degree by wide-angle X-ray diffraction. The X-ray diffraction image is used to measure the orientation degree. By using a fiber sample stage, 2θ is fixed at a peak near 18 °, the sample is rotated 360 ° (β-rotation), and the intensity distribution is measured along the Debye ring. From the intensity distribution obtained, the orientation degree of the surface layer is obtained using the following formula.
[0223] H={(360-ΣW / 360)}×100
[0224] In the formula, H represents the degree of orientation (%), and W represents the half width. The half width refers to the half width of a peak obtained from two peaks derived from the vicinity of 2θ=18°, one peak appears at a β-rotation angle in the range of 0° to 180°, and the other peak appears at a β-rotation angle in the range of 180° to 360°.
[0225] A rotating cathode type X-ray diffraction apparatus RINT 2500 (X-ray: CuKα) was used as an X-ray diffraction apparatus, and measurement was performed at a tube voltage of 40 kV and a tube current of 15 mA.
[0226] Method for measuring the thickness of the surface layer
[0227] The thickness of the surface layer was measured using a high-precision digital micrometer (MDH-25MC, manufactured by Mitutoyo Corporation), and the arithmetic mean of measurements at 5 points was used for the measurement result.
[0228] Evaluation Method
[0229] Next, the evaluation method in this embodiment is described.
[0230] Evaluation 1: Durability against chemical cracking
[0231] Evaluation was performed using the prepared fixing device. The evaluation conditions were as follows.
[0232] Test environment: room temperature 10℃, humidity 10%
[0233] Processing speed: 280mm / sec
[0234] Printing speed: 60 sheets / min
[0235] Paper feeding conditions: A web image was formed on copy paper (trade name: GF-C104; manufactured by Nippon Paper Industries Co., Ltd., 105 g paper, A4 size), and the paper was continuously fed.
[0236] Copy paper (trade name: GC-C081; manufactured by Nippon Paper Industries Co., Ltd., 68 g paper, A4 size) was fed every 100,000 sheets, and the occurrence of scratches (chemical cracks) in the length direction of the surface layer after the feeding was observed and evaluated according to the following criteria.
[0237] Evaluation Criteria
[0238] Rank A: Even after feeding 500,000 sheets, the occurrence of chemical cracks was not observed on the surface layer.
[0239] Rank B: The number of sheets that have been fed at the time when the occurrence of chemical cracks on the surface layer was first observed was 400,000 sheets or more and less than 500,000 sheets.
[0240] Rank C: The number of sheets that have been fed at the time when the occurrence of chemical cracks on the surface layer was first observed was 300,000 sheets or more and less than 400,000 sheets.
[0241] Rank D: The number of sheets that had been fed at the time when the occurrence of chemical cracks on the surface layer was first observed was less than 300,000 sheets.
[0242] Evaluation 2: Durability evaluation
[0243] Evaluation of wear resistance
[0244] The prepared fixing device was subjected to a wear resistance test under the following conditions and evaluated according to the following criteria.
[0245] condition
[0246] Test environment: room temperature 25℃, humidity 50%
[0247] Processing speed: 280mm / sec
[0248] Printing speed: 60 sheets / min
[0249] Paper feeding conditions: A grid image was formed on copy paper (trade name: CS-068; manufactured by Nippon Paper Industries Co., Ltd., 68 g paper, A4 size), and the paper was continuously fed.
[0250] Evaluation Criteria
[0251] A: Even after 500,000 sheets of paper had been fed, no abrasion was observed on the surface layer.
[0252] B: Even after 200,000 sheets of paper had been fed, no abrasion was observed on the surface layer, but after 500,000 sheets of paper had been fed, slight abrasion caused by the end portions of the paper was observed on the surface layer.
[0253] C: After 200,000 sheets of paper have been fed, slight wear caused by the end of the paper is observed on the surface layer. In addition, after 500,000 sheets of paper have been fed, significant wear caused by the end of the paper is observed on the surface layer.
[0254] D: Significant abrasion caused by the end portions of the paper is observed on the surface layer after 200,000 sheets of paper have been fed.
[0255] Evaluation of motor torque current value
[0256] In addition to the above evaluation of wear resistance, the motor torque current value during paper feeding was measured every 100,000 sheets of paper fed, and evaluation was performed under the following evaluation criteria: A small motor torque current value means that the heat resistance of the grease is excellent.
[0257] Evaluation Criteria
[0258] Level A: Motor torque is less than 2.0A
[0259] Level B: Motor torque is 2.0A or more and less than 2.5A
[0260] Level C: Motor torque is 2.5A or more and less than 3.0A
[0261] Level D: Motor torque is 3.0A or more
[0262] Example 2
[0263] A fixing film was obtained in the same manner as in Example 1, except that the cooling rate of the heating tube in the heating treatment of the surface layer was changed to a rate of 60° C. / min. A fixing device was prepared using the obtained fixing film.
[0264] Example 3
[0265] A fixing film was obtained in the same manner as in Example 1 except that the heating control temperature of the heating tube in the heating treatment of the surface layer was changed to 320° C. A fixing device was prepared using the obtained fixing film.
[0266] Example 4
[0267] Except that the thickness of the surface layer was changed to 10 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was prepared using the obtained fixing film.
[0268] Example 5
[0269] Except that the thickness of the surface layer was changed to 100 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was prepared using the obtained fixing film.
[0270] Example 6
[0271] A fixing film was obtained in the same manner as in Example 1, except that the cooling rate of the heating tube in the heating treatment of the surface layer was changed to a rate of 10° C. / min. A fixing device was prepared using the obtained fixing film.
[0272] Example 7
[0273] Except that the thickness of the surface layer was changed to 5 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was prepared using the obtained fixing film.
[0274] Example 8
[0275] Except that the thickness of the surface layer was changed to 110 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was prepared using the obtained fixing film.
[0276] Example 9
[0277] Except that the thickness of the surface layer was changed to 5 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was prepared using the obtained fixing film.
[0278] Comparative Example 1
[0279] Except that the surface layer was not subjected to heat treatment, a fixing film was obtained in the same manner as in Example 1. A fixing device was prepared using the obtained fixing film.
[0280] Comparative Example 2
[0281] A fixing film was obtained in the same manner as in Example 1, except that the cooling rate of the heating tube in the heating treatment of the surface layer was changed to a rate of 70° C. / min. A fixing device was prepared using the obtained fixing film.
[0282] Comparative Example 3
[0283] A fixing device was prepared in the same manner as in Example 1, except that silicone grease (trade name: G-501; manufactured by Shin-Etsu Silicone Co., Ltd.) was used instead of the fluorine grease.
[0284] Comparative Example 4
[0285] A fixing film and a fixing device were prepared in the same manner as in Example 1, except that “959HP-PLUS” (trade name, manufactured by The Chemours Company) was used instead of “AP-231SH”, and silicone grease G-501 (manufactured by Shin-Etsu Silicone Co., Ltd.) was used instead of fluorine grease as the raw materials for the surface layer.
[0286] The results of Examples 1 to 9 and Comparative Examples 1 to 4 are summarized in Tables 1 and 2.
[0287] [Table 1]
[0288]
[0289] [Table 2]
[0290] Chemical crack Wear resistance Motor torque Example 1 A A A Example 2 A C A Example 3 B A A Example 4 A B A Example 5 A B A Example 6 B A A Example 7 C A A Example 8 A C A Example 9 A C A Comparative Example 1 D A A Comparative Example 2 A D A Comparative Example 3 A A D Comparative Example 4 A D D
[0291] The fixing device produced by the method disclosed in this embodiment can achieve both wear resistance and durability against chemical cracks.
[0292] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A fixing device, comprising: A fixing film having a ring shape, a pressing member disposed to face the fixing film and configured to form a nip with the fixing film, and a heating member disposed inside the fixing film, having an opposing surface facing the inner peripheral surface of the fixing film and configured to cause the fixing film to apply a force to the pressing member, and Fluorine grease inserted between the inner peripheral surface and the facing surface, wherein The fixing film comprises at least a base layer, an elastic layer, and a surface layer in sequence. The surface layer comprises tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer PFA, The surface layer includes a plurality of spherulites of the PFA, and In an endothermic curve measured by a differential scanning calorimeter DSC at a temperature increase rate of 20° C. / min using a sample sampled from the surface layer as a measurement sample, an endothermic amount in a temperature increase process is 21 J / g or more.
2. The fixing device according to claim 1, wherein The amount of heat absorbed during the temperature increase process is less than 40 J / g.
3. The fixing device according to claim 1 or 2, wherein: The degree of orientation of PFA molecules in a direction orthogonal to the circumferential direction of the surface layer obtained using a transmission X-ray diffraction method is 35% or less.
4. The fixing device according to claim 1 or 2, wherein: The thickness of the surface layer is in the range of 10 to 100 μm.
5. The fixing device according to claim 1 or 2, wherein: The fluorine grease includes fluorine resin particles and fluorinated oil.
6. An electrophotographic image forming apparatus comprising: A fixing device according to any one of claims 1 to 5.
Citation Information
Patent Citations
Image forming device
JP1988313182A
Image heat fixing device
JP1990157878A
Image-fixing device
JP2007187889A
